Implementasi Ajaran Catur Purusha Artha Dalam Membentuk Karakter Anak Panti Asuhan Ananda Sevadharma Dusun Banjar Sema Desa Sangsit - Krisna Danuartha; Ni Komang Candrani Dewi (Pramana: Jurnal Hasil Penelitian, 2023)
This article discusses the implementation of the Catur Purusha Arthadoctrine in shaping the character of children in the Narayan Seva Orphanage. This doctrine encompasses the values of Dharma (morality and spirituality), Artha (economics and material), Kama (aesthetics and happiness)and Moksa (highest goal) which are applied in the character education of children in orphanages, which are applied in the character education of children in the orphanage. In the face of modern challenges, this article explains how the values of Dharma are instilled through moral and ethical education, the values of Artha are applied through financial education and responsible ownership, and the values of Kama are realized through the development of interests and talents. Despite challenges such as adapting ancient values to modern contexts, collaborating with families, and monitoring effectiveness, the Narayan Seva Orphanage has created an environment focused on fostering positive and integral character through the implementation of the Catur Purusha Arthadoctrine. Thus, this article summarizes that this approach can shape a generation ready to face the world wisely and make a positive contribution to society.